Density functional theory approach to CO2 adsorption on a spinel mineral: determination of binding coordination. Issue 34 (18th March 2016) - Moon, Hye Sook; Kwon, Soonchul; Kwon, Sung Hyun; Cho, Min; Seo, Jeong Gil; Lee, Seung Geol
Abstract : Adsorption mechanisms of CO2 on MgAl2 O4 (100) surface. Abstract : The mechanism of the adsorption of CO2 onto various sites of MgAl2 O4 (100), in particular with regards to binding coordination, was investigated using density functional theory (DFT) calculations. Of the available sites, CO2 binding was calculated to be strongly adsorbed to oxygen atoms on the octahedral Al 3+ and tetrahedral Mg 2+ sites, with adsorption energy values of −1.60 eV and −1.86 eV, respectively, which was attributed to the small band gap of the CO2 –MgAl2 O4 system. It is clearly found that strongly adsorbed CO2 molecules bound to MgAl2 O4 using polydentate ( e.g., bidentate and tridentate) bonds. We also simulated the adsorption of multiple CO2 molecules on MgAl2 O4, and found three of eight CO2 molecules to be strongly adsorbed using tridentate bonds onto the MgAl2 O4 surface, with an interaction energy of −0.61 eV. The other five CO2 molecules were also adsorbed, but weakly, i.e., using physical interactions with a modest binding energy of <0.10 eV and at a relatively long distance from the MgAl2 O4 surface.